Potential of Inulin-Fructooligosaccharides Extract Produced from Red Onion (Allium cepa var. viviparum (Metz) Mansf.) as an Alternative Prebiotic Product - Jakkrit Aisara; Pairote Wongputtisin; Somkid Deejing; Chutamas Maneewong; Kridsada Unban; Chartchai Khanongnuch; Paul Kosma; Markus Blaukopf; Apinun Kanpiengjai (Plants, 2021)
Red onion is a popular ingredient in many Thai dishes and has recently been promoted for commercial cultivation. In this study, inulin-fructooligosaccharides (inulin-FOSs) were extracted from red onions in a simplified extraction method. The extract contained 24.00 ± 0.38 g/L free glucose, fructose and sucrose, while the level of FOSs was recorded at 74.0 ± 2.80 g/L with a degree of polymerization of 4.1. The extract was resistant to simulated gastrointestinal conditions, while selectively promoting probiotic lactobacilli. These outcomes resulted in inhibitory effects against various pathogenic bacteria. The in vitro batch culture fermentation of the extract by natural mixed culture indicated that an unknown sugar identified as neokestose was more rapidly fermented than 1-kestose and other longer-chain inulin-FOSs. Notably, neokestose selectively encouraged a bifidogenic effect, specifically in terms of the growth of Bifidobacteirum breve, which is an infant-type probiotic bacterium. This is the first report to state that neokestose could selectively enhance the bifidogenic effect. In summary, inulin-FOSs extract should be recognized as a multifunctional ingredient that can offer benefits in food and pharmaceutical applications.